Peran Associate Producer dalam Menciptakan Keunikan Program Magazine Daily Lifestyle di Okezone TV - Maulaniah, Suci; Soraya, Iin; Yunita Pratiwi, Cindya (UNIVERSITAS SERAMBI MEKKAH, 2025)
Okezone TV is part of MNC Channels, featuring various flagship programs, one of which is Daily Lifestyle. This program has successfully captured viewers’ attention due to its uniqueness in content and presentation. Its success is closely linked to the crucial role of the Associate Producer, who is involved throughout the production process. This study employs a qualitative descriptive method with data collection techniques such as in-depth interviews, observations, and documentation. The findings indicate that the Associate Producer plays a significant role in creating the program’s uniqueness, mainly through creativity and effective coordination with the production team. The innovative approaches applied during the production process are key factors in Daily Lifestyle’s success in maintaining its appeal amidst the competitive television industry.